Metal-containing and Related Polymers for Biomedical Applications - Yan, Yi (Chem Soc Rev, 2016)
A survey of the most recent progress in the biomedical applications of metal-containing polymers is given. Due to the unique optical, electrochemical, and magnetic properties, at least 30 different metal elements, most of them transition metals, are introduced into polymeric frameworks for interactions with biology-relevant substrates via various means. Inspired by the advance of metal-containing small molecular drugs and promoted by the great progess in polymer chemistry, metal-containing polymers have gained momentum during recent decades. According to their different applications, this review summarizes the following biomedical applications: 1) metal-containing polymers as drug delivery vehicles; 2) metal-containing polymeric drugs and biocides, including antimicrobial and antiviral agents, anticancer drugs, photodynamic therapy agents, radiotherapy and biocide; 3) metal-containing polymers as biosensors, and 4) metal-containing polymers in bioimaging.